Hot Molecules, Cold Electrons : From the Mathematics of Heat to the Development of the Trans-Atlantic Telegraph Cable - Nahin, Paul J. (Princeton University Press, 2020)
An entertaining mathematical exploration of the heat equation and its role in the triumphant development of the trans-Atlantic telegraph cableHeat, like gravity, shapes nearly every aspect of our world and universe, from how milk dissolves in coffee to how molten planets cool. The heat equation, a cornerstone of modern physics, demystifies such processes, painting a mathematical picture of the way heat diffuses through matter. Presenting the mathematics and history behind the heat equation, Hot Molecules, Cold Electrons tells the remarkable story of how a foundational idea brought about one of the greatest technological advancements of the modern era.Paul Nahin vividly recounts the heat equation's tremendous influence on society, showing how French mathematical physicist Joseph Fourier discovered, derived, and solved the equation in the early nineteenth century. Nahin then follows Scottish physicist William Thomson, whose further analysis of Fourier's explorations led to the groundbreaking trans-Atlantic telegraph cable. This feat of engineering reduced the time a message could be sent across the ocean from weeks to minutes. Readers also learn that Thomson used Fourier's solutions to calculate the age of the earth, and, in a bit of colorful lore, that writer Charles Dickens relied on the trans-Atlantic cable to save himself from a career-damaging scandal. The book's mathematical and scientific explorations can be easily understood by anyone with a basic knowledge of high school calculus and physics, and MATLAB code is included to aid readers who would like to solve the heat equation themselves.A testament to the intricate links between mathematics and physics, Hot Molecules, Cold Electrons offers a fascinating glimpse into a formative equation's relationship with one of the most important developments in human communication.